Stress Levels Among Nurses Working in the Emergency Department and Their Work Motivation During the COVID-19 Pandemic at Level IV Military Hospital 01.07.01 Pematangsiantar - Rovina Efranti Barus; Isa Harpika Ginting; Tati Adriana Saragih (Benih : Journal of Midwifery, 2025)
Nurses' work stress during the COVID-19 pandemic has been a significant factor contributing to decreased job performance, primarily due to excessive workloads and lack of motivation. Therefore, providing work motivation to nurses is crucial. This study aims to analyze the relationship between stress levels and work motivation among nurses working in the Emergency Department during the COVID-19 pandemic at Level IV Military Hospital Pematangsiantar. This research used a quantitative method with a cross-sectional approach. The population was selected using a total sampling technique, consisting of 25 respondents. The variables in this study were stress levels and work motivation. Data were collected using a questionnaire, and data processing involved editing, coding, scoring, and tabulating. Data were analyzed using Spearman’s Rho rank test. The study found that nearly half of the respondents experienced a moderate level of stress (12 respondents or 48%), and nearly half had a moderate level of work motivation (12 respondents or 44%). The statistical test showed a p-value of 0.000 < α = 0.005, indicating that H1 is accepted. There is a significant relationship between the stress levels of nurses working in the Emergency Department and their work motivation during the COVID-19 pandemic at Level IV Military Hospital Pematangsiantar.